2019
DOI: 10.1002/fam.2735
|View full text |Cite
|
Sign up to set email alerts
|

The discrepancies in energy balance in furnace testing, a bug or a feature?

Abstract: Summary The paper aims to explain the differences found in the heat release rate measurements in a large sample of standard fire tests (EN 1363‐1). A total of 379 tests of vertical assemblies was investigated, all performed in furnace SPARK of the ITB Fire Testing Laboratory, in 2015‐2018. The assemblies were subdivided into two groups—wall assemblies and fire‐rated doors. These assemblies were also compared with the results of the test of a wall built with aerated autoclaved concrete blocks that was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A recent top-down study of facade fire incidents found, among other things, that 17% of incidents recorded involved fatalities [17]. Another top-down study used large numbers of commercial furnace test data to analyse the discrepancies in energy balance in the testing approach [18]. Machine Learning has also be suggested as a way to gain more information from commercial fire tests, rather than only a strict classification [19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent top-down study of facade fire incidents found, among other things, that 17% of incidents recorded involved fatalities [17]. Another top-down study used large numbers of commercial furnace test data to analyse the discrepancies in energy balance in the testing approach [18]. Machine Learning has also be suggested as a way to gain more information from commercial fire tests, rather than only a strict classification [19].…”
Section: Introductionmentioning
confidence: 99%
“…If we consider the tests methods according to the scheme in Figure 1, most of them, and above all methods used for validation of models or for the purpose of solving scientific issues are rather individual and developed for a specific need. Examples of such individual tests are on macro-scale the experimental and numerical methods used to study the mechanical behavior of objects at a natural scale (e.g., [3,4]), fire tests of walls or doors [5]. Micro-scale tests are among others scientific methods based on advanced material research, such as X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM) (e.g., [6][7][8]), and other advanced methods used to understand the mechanisms of phenomena occurring from the macro to the nano-scale.…”
Section: Introductionmentioning
confidence: 99%
“…However, the standard temperature-time curve and furnace tests are based on convention and were not conceived with combustible structures in mind [12]. For example, when a combustible member is burning in a furnace the amount of energy has to be reduced to follow the same standard fire curve as for combustible members [13,14]. Lately, there has been an increasing trend towards a more performance-based approach in structural fire engineering, for example, by using a range of temperature-time curves.…”
Section: Introductionmentioning
confidence: 99%